FAKTOR-FAKTOR YANG MEMPENGARUHI AKSEPTOR KB DALAM PEMILIHAN KONTRASEPSI MKJP DI TEMPAT PRAKTEK MANDIRI BIDAN JABA KELURAHAN KESIMAN DENPASAR TIMUR - Ni Ketut Noriani (JURNAL MEDIKA USADA, 2023)
One indicator of the success of a country's development is determined based on the quality of Human Resources (HR). This is indicated by the still high birth rate every year. The fast rate of population growth will slow down the achievement of ideal conditions between the quality and quantity of a person with inadequate carrying capacity and environmental capacity, making it difficult to increase and distribute people's welfare (BKKBN, 2019). . The decision-making role relates to the selection of contraceptives (Astuti and Holidi, 2015). Sources of information regarding the type or means of contraception can be obtained from community leaders, health workers, mass media and families who have an important role for couples of childbearing age (PUS) (Rachmayani, 2015). The role of health workers is related to the selection of contraceptives because they are considered to play a very important role in the final stage of choosing contraceptives (Andrianasti, 2014). The role of health workers is related to the selection of contraceptives because they are considered to play a very important role in the final stage of selecting contraceptives (Wulandari et al., 2016) The purpose of this study was to determine the factors that influenced family planning acceptors to choose KB MKJP at BPM JABA, Kesiman Village, East Denpasar. This type of research is a descriptive study with a cross sectional design. The results showed that the determinant factors (education, knowledge, husband's support) influence a person's attitude in making a decision to determine the choice of contraception to be used. The choice of contraception is influenced by economic factors, because the economy is related to the availability of funds in obtaining services for contraceptives that are chosen appropriately according to needs and desires.